Powers, engagements and resultant influences over the design and implementation of medicine pricing policies in Ghana. Issue 5 (19th May 2022) - Koduah, Augustina; Baatiema, Leonard; Kretchy, Irene A; Agyepong, Irene Akua; Danso-Appiah, Anthony; de Chavez, Anna Cronin; Ensor, Timothy; Mirzoev, Tolib
Abstract : Introduction: Universal availability and affordability of essential medicines are determined by effective design and implementation of relevant policies, typically involving multiple stakeholders. This paper examined stakeholder engagements, powers and resultant influences over design and implementation of four medicines pricing policies in Ghana: Health Commodity Supply Chain Master Plan, framework contracting for high demand medicines, Value Added Tax (VAT) exemptions for selected essential medicines, and ring-fencing medicines for local manufacturing. Methods: Data were collected using reviews of policy documentation (n=16), consultative meetings with key policy actors (n=5) and in-depth interviews (n=29) with purposefully identified national-level policymakers, public and private health professionals including members of the National Medicine Pricing Committee, pharmaceutical wholesalers and importers. Data were analysed using thematic framework. Results: A total of 46 stakeholders were identified, including representatives from the Ministry of Health, other government agencies, development partners, pharmaceutical industry and professional bodies. The Ministry of Health coordinated policy processes, utilising its bureaucratic mandate and exerted high influences over each policy. Most stakeholders were highly engaged in policy processes. Whereas some led or coproduced the policies in the design stage and participated in policy implementation, others were consulted for their inputs, views and opinions. Stakeholder powers reflected their expertise, bureaucratic mandates and through participation in national level consultation meetings, influences policy contents and implementation. A wider range of stakeholders were involved in the VAT exemption policies, reflecting their multisectoral nature. A minority of stakeholders, such as service providers were not engaged despite their interest in medicines pricing, and consequently did not influence policies. Conclusions: Stakeholder powers were central to their engagements in, and resultant influences over medicine pricing policy processes. Effective leadership is important for inclusive and participatory policymaking, and one should be cognisant of the nature of policy issues and approaches to policy design and implementation.